Novel routes for ceramics synthesis and processing : 12th International Ceramics Congress, Part B : proceedings of the 12th International Ceramics Congress, part of CIMTEC 2010--12th International Ceramics Congress and 5th Forum on New Materials, Montecatini Terme, Italy, June 6-11, 2010 - International Meeting on Modern Ceramics Technologies (12th : 2010 : Montecatini Terme, Italy); Vincenzini, P., 1939-; Forum on New Materials (5th : 2010 : Montecatini Terme, Italy) (Stafa-Zuerich, Switzerland ; Enfield, NH, USA : Trans Tech Publications Ltd., on behalf of Techna Group, Faenza, Italy)
Includes bibliographical references and indexes